2012
DOI: 10.1111/j.1365-246x.2012.05596.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective shear and bulk viscosity of partially molten rock based on elastic moduli theory of a fluid filled poroelastic medium

Abstract: SUMMARY The effective bulk and shear viscosity of the matrix of a partially molten rock are important properties for the process of melt migration and matrix compaction. A set of porosity‐dependent effective bulk and shear viscosity models is presented based on a self‐consistent poroelastic formulation for partially molten rock where the melt occurs in spherical, ellipsoidal, film‐like or tubular inclusions. For these melt geometries a graphical user interface operated MATLAB program is provided which allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 29 publications
3
63
0
Order By: Relevance
“…This is expected, as our formulation only addresses the increase of ξ as the porosity φ → 0. However, this sensitivity to ξ/η might not be problematic for realistic applications, as this ratio is expected to be on the order of 1-100 (Hewitt & Fowler 2008;Takei & Holtzman 2009;Simpson et al 2010;Katz 2010;Schmeling et al 2012;Alisic et al 2014).…”
Section: Influence Of Materials Propertiesmentioning
confidence: 99%
“…This is expected, as our formulation only addresses the increase of ξ as the porosity φ → 0. However, this sensitivity to ξ/η might not be problematic for realistic applications, as this ratio is expected to be on the order of 1-100 (Hewitt & Fowler 2008;Takei & Holtzman 2009;Simpson et al 2010;Katz 2010;Schmeling et al 2012;Alisic et al 2014).…”
Section: Influence Of Materials Propertiesmentioning
confidence: 99%
“…Recently, Schmeling et al . [] numerically derived effective shear and bulk viscosities in purely viscous rocks with singular cavities of various geometries. They showed that spherical and ellipsoidal inclusions lead to ηb=c1ηs()c2φkφwhere parameters c 1 , c 2 , and k depend on the melt geometry.…”
Section: Comparison To the Previous Modelsmentioning
confidence: 99%
“…Effects of nonconstant fluid/solid densities in triggering porosity waves and fluid networks during metamorphism are investigated in two recent studies (Malvoisin et al, 2015;Pl€ umper et al, 2017); this study, however, focuses on advective heat transport after porosity waves are triggered and evolve into channels. In addition, shear deformation is neglected as in previous studies to focus on volumetric compaction/decompaction (Connolly & Podladchikov, 2007;Spiegelman et al, 2001), but shear viscosity is considered because bulk viscosity depends on it via equation (6) (Hier-Majumder et al, 2006;Schmeling et al, 2012;Simpson et al, 2010). Notations for symbols are given in Table 1.…”
Section: Governing Equationsmentioning
confidence: 99%